1993
DOI: 10.1007/bf03160872
|View full text |Cite
|
Sign up to set email alerts
|

Responses of forested wetland vegetation to perturbations of water chemistry and hydrology

Abstract: Nineteen mature Atlantic white-cedar swamps, located in four categories of undeveloped and suburban watersheds of the New Jersey Pinelands, were studied to determine the relationship between perturbations of water quality and hydrology and changes in species composition and community structure. Rank-orders of the 19 sites were compared for key variables (ground-water and surface-water NH4 and PO4, mean water-table level and water-table range). Rank orders for the sites were different for the various parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…One of the most visible aspects of altered structure is the invasion of native communities by non-native plant species (Kusler 1988, McColligan and Kraus 1988, Ehrenfeld and Schneider 1993. Although the threat to native diversity posed by introduced species is well-documented, the extent to which the flora of wetlands in urban settings is diluted by introduced species has received less attention.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the most visible aspects of altered structure is the invasion of native communities by non-native plant species (Kusler 1988, McColligan and Kraus 1988, Ehrenfeld and Schneider 1993. Although the threat to native diversity posed by introduced species is well-documented, the extent to which the flora of wetlands in urban settings is diluted by introduced species has received less attention.…”
Section: Introductionmentioning
confidence: 98%
“…Although the threat to native diversity posed by introduced species is well-documented, the extent to which the flora of wetlands in urban settings is diluted by introduced species has received less attention. For some wetland ecosystems, the influx of introduced plant species has been shown to be associated with altered hydrology and increasing intensity of surrounding land-use (Cooke and Azous 1993, Ehrenfeld and Schneider 1993, Taylor 1993, Houck 1996. Intensified land-use adjacent to wetlands or in associated stream drainage ways can result in physical changes to wetland environments that may affect plant species assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture, land-use conversion and fragmentation are the most obvious landscape scale disturbances to floodplains ͑McIntyre and Nancy 1991; Cole et al 1997;Wardrop and Brooks 1998͒. Timber harvest in a watershed can alter the total flow, peak discharge rate, and the frequency and duration of flows within a stream ͑Troendle and Olsen 1994͒, and urbanization has been associated with hydrologic changes in wetlands ͑Taylor 1993; Ehrenfeld and Schneider 1993;Ewing 1996͒. On a longer time scale, Hupp et al ͑1993͒ found substantial increases in sedimentation rates in a forested floodplain over the past 50 years, with the highest rates directly downstream from urban-industrialized areas.…”
Section: Introductionmentioning
confidence: 99%
“…These will provide low levels of necessary nutrients over time. Higher dissolved nutrient levels, such as could occur if rapid release fertilizer were used, promote invasion by vegetation not characteristic of a healthy white cedar community (Ehrenfeld & Schneider 1991, 1993). Given the recent demonstration of natural colonization of C. thyoides by mycorrhizal fungi (Cantelmo & Ehrenfeld 1999) and the ability of such colonization to augment the mineral nutrition of the host plant in poor soils (Harley & Smith 1983), inoculation of the soil or planted trees with mycorrhizae might further increase the success of C. thyoides on new sites.…”
Section: Discussionmentioning
confidence: 99%